Digital model for Sugarcane Production for the Factory in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The paper aimed to study and to assess digital model for sugarcane production for the factory in Thai supply chain . The samples are ten experts in the field of information and supply chain. The data is analysed by means and standardized deviations. The research about digital model for sugarcane production for the factory in Thai supply chain consists of eight elements namely main components Suppliers , Factory (Manufacture) Distribution Wholesaler Consumers and Satisfaction. The assessment about digital model for sugarcane production for the factory in Thai supply chain using Black-Box technique. The research findings revealed that digital model for sugarcane production for the factory in Thai supply chain is appropriate at the high level and can be applied in support the tasks.